Nanoparticle Synthesis of Secang Wood Extract (Caesalpinia sappan L.) as Antibacterial Agent - Dedek Febbriani; Tita Juwitaningsih; Amalia Anggreni Br Ginting; Annisya Dwi Putri Zulmi; Sasi Kirana; Peggy Ananda Putri Adi Yunita; Frengky Sanjaya Ginting (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Abstract. Indonesia is a country rich in various types of plants that can be used as medicinal ingredients, including traditional medicine, herbs, and jamu. The sappanwood plant is one of the widely used plants in traditional medicine. The sappanwood plant contains chemicals such as flavonoids, brazilin, alkaloids, saponins, tannins, phenylpropane, and terpenoids. The need for metabolite compounds has recently increased significantly to overcome resistance to bacteria. Infectious diseases in Indonesia are still among the ten highest diseases, so in 2050 deaths due to antibiotic resistance will reach 10 million per year and become the highest cause of death among other causes. The methodology of this study began with sample preparation, making sappanwood extract, isolating secondary metabolite compounds using preliminary TLC, synthesizing nanoparticles using the ionic gelation method, and testing antibacterial activity using P. acnes and P. aeruginosa bacteria. The results of the study revealed that the synthesis of nanoparticles showed moderate antibacterial activity with an inhibition zone of 8.15 mm against P. acnes and 9.1 mm against P. aeruginosa. In contrast, ethyl acetate extract showed a stronger antimicrobial effect, reaching inhibition zones of 13.02 mm and 19.54 mm, respectively. This indicates that the activity shown is relatively strong due to the difference in concentration used during the study. It is expected that further research can produce a larger antibacterial inhibition zone than ethyl acetate extract.